Over-expression of Tgs1 in Mycobacterium marinum enhances virulence in adult zebrafish - Ding-qian Liu; Jun-li Zhang; Zhi-fen Pan; Jun-tao Mai; Heng-jun Mei; Yue Dai; Lu Zhang; Qing-zhong Wang (Elsevier, 2020)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), can persist in the host for decades without causing TB symptoms and can cause a latent infection, which is an intricate challenge of current TB control. The DosR regulon, which contains approximately 50 genes, is crucial in the non-replicating persistence of Mtb. tgs1 is one of the most powerfully induced genes in this regulon during Mtb non-replicating persistence. The gene encodes a triacyl glycerol synthase catalyzing synthesis of triacyl glycerol (TAG), which is proposed as an energy source during bacilli persistence. Here, western blotting showed that the Tgs1 protein was upregulated in clinical Mtb strains. To detect its physiological effects on mycobacterium, we constructed serial recombinant M. marinum including over-expressed Tgs1(Tgs1-H), reduced-expressed Tgs1(Tgs1-L), and wild type M. marinum strains as controls. Tgs1 over-expression did not influence M. marinum growth under aerobic shaking and in hypoxic cultures, while growth advantages were observed at an early stage under nutrient starvation. Transmission electron microscopy revealed more lipid droplets in Tgs1-H than the other two strains; the droplets filled the cytoplasm. Two-dimensional thin-layer chromatography revealed more phosphatidyl-myo-inositol mannosides in the Tgs1-H cell wall. To assess the virulence of recombinant M. marinum in the natural host, adult zebrafish were infected with Tgs1-H or wild type strains. Hypervirulence of Tgs1-H was characterized by markedly increased bacterial load and early death of adult zebrafish. Remarkably, zebrafish infected with Tgs1-H developed necrotizing granulomas much more rapidly and in higher amounts, which facilitated mycobacterial replication and dissemination among organs and eventual tissue destruction in zebrafish. RNA sequencing analysis showed Tgs1-H induced 13 genes differentially expressed under aerobiosis. Among them, PE_PGRS54 (MMAR_5307),one of the PE_PGRS family of antigens, was markedly up-regulated, while 110 coding genes were down-regulated in Tgs1-L.The 110 genes included 22 member genes of the DosR regulon. The collective results indicate an important role for the Tgs1 protein of M. marinumin progression of infection in the natural host. Tgs1 signaling may be involved in a previously unknown behavior of M. marinum under hypoxia/aerobiosis.